Adoption and impact of improved technologies in developing countries: the case of Imazapyrresistant maize in Western Kenya - Mignouna, Djana B. (Lambert Academic Publishing, 2012)
Declining productivity of food crops in developing countries is associated with several factors including poor adoption of improved technologies against pests and parasites destroying crops with developmental implications on food insecurity and poverty. This study has been undertaken to contribute to the understanding of farm-level adoption dynamics and economic impacts of agricultural technologies. This study was done using a case of imazapyr-resistant maize technology for combating noxious Striga weed which has devastating effects on maize production in western Kenya. A cross sectional survey that included randomly selected samples of 169 adopters and 431 non-adopters. The relevant data were collected and analysed using descriptive statistics, stochastic production frontier and tobit regression models. The net present value (US $21 680 402), benefit-cost ratio (4.77) and net benefits per capita (US $41 063) for imazapyr-resistant maize enterprise were attractive. However, its adoption rate was low, whereby about 28% of the surveyed households adopted the technology. The results from tobit model estimation indicate that farming experience, education of the household head, gap between maize production and consumption, farmer’s risk-taking, number of extension visits, lack of seeds, membership to social groups and imazapyrresistant maize’s effective dissemination pathway were found to be significant (P<0.05) in influencing the adoption decision. The results of impact assessment indicated that its adoption increased significantly (P<0.01) the frontier maize output. Imazapyr-resistant maize had succeeded in reducing Striga seed-bank hence significantly (P<0.05) raising productivity from 2.2 ton/ha (non- imazapyr-resistant maize) to 2.8 ton/ha (imazapyrresistant maize) with significant returns to land (US $173/hectare) and labour (US $8/man-day). Two main conclusions can be drawn from this study. First and foremost, is that the use of imazapyr-resistant maize is a promising option for farmers since this technology has been shown to be profitable compared with other maize varieties and, secondly, it has the potential to impact positively on poverty reduction in western Kenya. Therefore, its adoption deserves attention from policy makers who should: (a) Initiate new awareness campaign, improve the seed supply chain in order to broaden its adoption and (b) provide significant positive public investment for technology transfer to improve its effectiveness and efficiency.